EVALUASI SISTEM PENDIDIKAN SELAMA COVID-19 TERHADAP PSIKOLOGI MAHASISWA - Afriana Afriana (Asosiasi Ide Bahasa Kepri, 2021)
The Covid-19 virus disease affects the entire world, including the education system and its impact on students' psychology. The goal of this study is to learn how the education system transitioned from offline or face-to-face teaching learning to online teaching-learning mode at Putera Batam University for the teaching-learning process and semester exams via online during COVID-19. In this study, the descriptive qualitative approach was used to discover students' psychology in online learning. In order to overcome these issues, the purpose of this study is to provide a comprehensive picture of online teaching and learning activities taking place during the lockdown period, including the link between the change management process and online teaching and learning processes in the education system in the midst of the COVID-19 outbreak. Ongoing disruption and resumption of educational activities and discourse as normal procedures in the education system. The data were analyzed using Wile (Syahputri et al., 2020) and Miles Huberman and Saldana (2014). They were 110 students as respondents (B.Miles et al., 2014). The result found that students fatigued 100%, they felt headache, tired, shoulder sore 85%, demotivation 21%, withdrawal, and procrastination 70%, bad time management about 76%, and Feeling Isolated 85% and Uncertainty to what the lecturer/friends explain during the class 75%.